2014
DOI: 10.1016/j.jaci.2013.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of asthma control and lung function responsiveness to step 3 therapy in children with uncontrolled asthma

Abstract: Background Predictors of improvement in asthma control and lung function to STEP-3 therapy in children with persistent asthma have not been identified despite reported heterogeneity in responsiveness. Objective To evaluate potential predictors of asthma control and lung function responsiveness to STEP-3 therapy. Methods A post-hoc analysis from the Best Add-On Giving Effective Response (BADGER) study tested the association between baseline biological, asthma control, pulmonary function and demographic mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 26 publications
1
40
0
1
Order By: Relevance
“…For example, in children with uncontrolled asthma receiving step 3 treatment, an increased LTE 4 /FENO ratio predicts a more favorable response to montelukast. 26 In the current study it is of interest that urinary LTE 4 baseline levels were high in spite of current ICS use, suggesting that the patients in this study were relatively refractory to ICSs. ICSs have been shown to reduce urinary LTE 4 levels.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…For example, in children with uncontrolled asthma receiving step 3 treatment, an increased LTE 4 /FENO ratio predicts a more favorable response to montelukast. 26 In the current study it is of interest that urinary LTE 4 baseline levels were high in spite of current ICS use, suggesting that the patients in this study were relatively refractory to ICSs. ICSs have been shown to reduce urinary LTE 4 levels.…”
Section: Discussionmentioning
confidence: 74%
“…ICSs have been shown to reduce urinary LTE 4 levels. 26 Surprisingly, montelukast alone also seemed ineffective in reducing urinary LTE 4 levels, and if anything, levels increased during montelukast treatment and only decreased when roflumilast was added. No changes in numbers of circulating neutrophils, eosinophils, or other leukocytes were noted during the study, and no other significant trends in inflammatory markers were evident.…”
Section: Discussionmentioning
confidence: 96%
“…Exploratory analyses utilized rank-ordered logistic regression to examine other phenotypic characteristics that might predict patterns of treatment response. Pre-specified exploratory analyses focused on serum eosinophil cationic protein (ECP) levels 21 and urinary leukotriene E 4 (LTE 4 ) concentrations 26 as predictors of treatment response. Blood eosinophils, specific aeroallergen tests results, serum IgE and modified Asthma Predictive Index 27 (mAPI) status, defined by a history of 4 or more wheezing episodes plus one major criteria (parental history of asthma, physician-diagnosed atopic dermatitis, or allergic sensitization to ≥1 aeroallergen) or two minor criteria (allergic sensitization to milk, egg, or peanut, wheezing unrelated to colds, or blood eosinophils ≥4%), 28 were examined post-hoc as potential predictors.…”
Section: Discussionmentioning
confidence: 99%
“…Rabinovitch et al 94 evaluated potential predictors of asthma control and lung function responsiveness to step 3 therapy and noted that available measures, such as measurement of exhaled nitric oxide and even leukotriene E 4 , do not reliably predict response to step 3 therapy. 94 An analysis of the same study by Malka et al 95 reported that race/ethnicity along with eczema history could be associated with differential response to long-acting b-adrenergic agonist (LABA), increased ICS, and leukotriene receptor antagonist (LTRA) step-up therapy. LABA step-up therapy is the preferred step-up treatment in asthmatic children without eczema.…”
Section: Predicting Treatment Responsementioning
confidence: 99%